Maximum running intensities during English academy rugby union match-play. Issue 1 (2nd January 2019) - Read, Dale B.; Till, Kevin; Beasley, Grant; Clarkson, Michael; Heyworth, Rob; Lee, Joshua; Weakley, Jonathon J.S.; Phibbs, Padraic J.; Roe, Gregory A.B.; Darrall-Jones, Joshua; Jones, Ben
ABSTRACT: To quantify and compare the maximum running intensities during rugby union match-play. Running intensity was quantified using micro-technology devices (S5 Optimeye, Catapult) from 202 players during 24 matches (472 observations). Instantaneous speed was used to calculate relative distance (m·min −1 ) using a 0.1 s rolling mean for different time durations (15 and 30 s and 1, 2, 2.5, 3, 4, 5, and 10 min). Data were analysed using a linear mixed-model and assessed with magnitude-based inferences and effect sizes (ES). Running intensity for consecutive durations (e.g., 15 s vs. 30 s, 30 s vs. 1 min, etc.) decreased as time increased (ES = 0.48–2.80). Running intensity was lower in forwards than backs during all durations (−0.74 ±0.21 to −1.19 ±0.21). Running intensity for the second row and back row positions was greater than the front row players at all durations (−0.58 ±0.38 to −1.18 ±0.29). Running intensity for scrum halves was greater (0.46 ±0.43 to 0.86 ±0.39) than inside and outside backs for all durations besides 15 and 30 s. Front rowers and scrum halves were markedly different from other sub-positional groups and should be conditioned appropriately. Coaches working in academy rugby can use this information to appropriately overload the intensity of running, specific to time durations and positions.